Inovatif Saat Pandemi Covid Melalui Pelatihan Kewirausahaan Khas Perempuan Berbahan Sampah “Kolaborasi BUMDes dan Warga” - Vembri Aulia Rahmi; Hadi Ismanto; Muhammad Zainuddin Fathoni (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2020)
The waste condition that has not been resolved, followed by the PSBB program, has become a creative idea for community service through collaboration between academics, BUMDes and villagers and in collaboration with the Waste Bank Association. The selection of female participants in entrepreneurship training, because it is seen that women understand the waste better. Service methods using socialization and application practices are considered most effective in the implementation of entrepreneurship training based on women's specific knowledge. The results of service are conducive in the covid outbreak situation while still implementing physical distancing. Enthusiasm was high both by the BUMDes "Podho Joyo", Sidayu District, Gresik Regency and village women. Training on the concept of entrepreneurship is also provided by academics, so that through dedication can be an innovative solution for village welfare during a pandemic.